2019
DOI: 10.1080/14681366.2019.1566162
|View full text |Cite
|
Sign up to set email alerts
|

Silences in a climate of voicing: teachers’ perceptions of societal and self-silencing regarding sensitive historical issues

Abstract: This study explores the silencing and voicing of sensitive topics in history education from a cross-national and multilevel perspective. In this mixed-method study, we undertook a quantitative analysis of a 'teaching sensitive issues' questionnaire and qualitative analyses of history curricula and teachers' verbal responses. The findings show that most respondents were aware of societal and selfsilencing but were also committed to voicing and giving a voice to pupils. Focusing on the issues found to be most se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…This example also demonstrates another factor of sensitivity; trough students' social identifications diverse and conflicting moral perspectives may become apparent. Teachers often refer to the social or religious background of students when explaining the reasons for sensitivity (Savenije et al, 2022;Savenije & Goldberg, 2019). Taken together, trauma, social identity and moral values can give rise to emotional responses in the classroom.…”
Section: Reasons For Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This example also demonstrates another factor of sensitivity; trough students' social identifications diverse and conflicting moral perspectives may become apparent. Teachers often refer to the social or religious background of students when explaining the reasons for sensitivity (Savenije et al, 2022;Savenije & Goldberg, 2019). Taken together, trauma, social identity and moral values can give rise to emotional responses in the classroom.…”
Section: Reasons For Sensitivitymentioning
confidence: 99%
“…A Dutch study involving 1,117 teachers (Sijbers, 2015) reports that teachers feel competent to deal with tensions in their classrooms, but when teaching in the lower levels of secondary education, they do have trouble with topics such as anti-Semitism, Islam, and fundamentalism. In a study involving 82 Dutch history teachers, it was found that teachers are especially challenged by emotional responses and over-simplified opinions in the classroom on topics such as Islam, the Holocaust and slavery (Savenije et al, 2022;Savenije & Goldberg, 2019). Two exploratory studies (De Graaff et al, 2016;Kleijwegt, 2016) report that student teachers and teachers in pre-vocational secondary education do not feel competent to teach sensitive topics because they have not fully developed their role as moral educator.…”
Section: Reasons For Sensitivitymentioning
confidence: 99%
“…Teachers try to influence the classroom’s emotional environment through pedagogical decision making (Knight-Diop & Oesterreich, 2009; Sheppard & Levy, 2019). Social studies teachers often try to create and maintain what they view as an emotionally safe and comfortable learning environment for themselves and students, which can lead to the omission of controversial and difficult content from the curriculum (Gibbs, 2019; Hostetler & Neel, 2018; Rodriguez, 2020; Savenije & Goldberg, 2019; Vickery et al, 2022). Teachers will avoid teaching about difficult histories if teaching such history makes them uncomfortable or anxious, if they disagree with how the history is framed, or if they fear students’ emotional reactions (Zembylas, 2016).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Teachers might be forced by the government, the curriculum or their school director to maintain silence, or they might opt to ignore and resist the norms of silencing (Brauch 2017). However, teachers can also silence topics as an act of self-censorship (Evans et al 1999), even if the topic appears in the curriculum or does not incur sanctions by society in general (Savenije and Goldberg 2019).…”
Section: Another Teacher Commented Thatmentioning
confidence: 99%